The linguistic landscape of Malaga: between globalization and local identity - Esteba-Ramos, Diana; Sáez Rivera, Daniel M. (My University, 2017)
Following a preliminary study on the Linguistic Landscape of Malaga (Esteba Ramos, 2014; Esteba Ramos/Sáez Rivera, 2014), some issues deserve further research, and some of these can be most appropriately depicted on a poster containing photographs. On one hand, the Málaga Linguistic Landscape shows traits of globalization, with the presence of several languages (mainly but not only English) especially in the city center, owing to tourism, and a surprising scarcity of immigrant languages and Spanish American varieties (e.g., the Silent LL pattern established by Castillo/Sáez, 2011; Sáez/Castillo, 2012). English, however, is also present in urban art graffiti, signs for businesses, and numerous services (e.g., lawyers, real estate, health services) are offered to permanent or long-term residents in many foreign languages. On the other hand, local identity is publicly showcased in the form of written representations of phonic and lexical traits of the Spanish spoken in Málaga, e.g., bars named “Er Compá” or “Er Quezada”, and menus offering “nubes” (coffee with milk), “campero” (Málaga’s characteristic sandwich of ham and toppings such as lettuce, tomato, cheese and mayonnaise sauce) or “pitufos” (small sandwiches). The latter phenomenon has been also observed in another town in Andalucía (see Pons Rodríguez, 2011). Loanwords like Arabic “shawarma”, “showarma” or even “chouorma” in the same street menus are a bridge between local and global Linguistic Landscape in Málaga. Keywords: Linguistic Landscape, globalization, local identity, loanwords, Málaga References (selected) Castillo Lluch, Mónica / Sáez Rivera, Daniel M. (2011): «Introducción al paisaje lingüístico de Madrid», Lengua y Migración 3, pp. 73-88. <http://dspace.uah.es/dspace/bitstream/handle/10017/10822/introduccion_castillo_LM_2011.pdf?sequence=1> Esteba Ramos, Diana (2014): "Aproximación al paisaje lingüístico de Málaga: préstamos y reflejos de una realidad lingüística plural", Recherches (Université de Strasbourg) 7, pp. 165-187. Esteba Ramos, Diana / Sáez Rivera, Daniel M. (2014): “A Comparison of Immigrant Languages and Varieties in the Linguistic Landscape of Two Towns in Spain: Madrid vs. Málaga”, Linguistic Landscapes 6, “Hope and Precarity,” 9-11 April 2014, Cape Town, South Africa (University of the Western Cape) <http://riuma.uma.es/xmlui/bitstream/handle/10630/7482/Presentation%20Cape%20Town%20DEf.pdf?sequence=3> Pons Rodríguez, Lola (2011): El paisaje lingüístico de Sevilla. Sevilla: Diputación de Sevilla. Sáez Rivera, Daniel M. /Castillo Lluch, Mónica (2012): «The Human and Linguistic Landscape of Madrid (Spain)», C.Hélot, M. Barni, R. Janssens & C. Bagna (eds.), Linguistic Landscapes, Multilingualism and Social Change: Diversité des approches, Bern, Peter Lang, pp. 309-328.
Keywords: Español - Andalucía; Paisaje Lingüístico; Lengua Española; Globalización; Identidad local; Préstamos lingüísticos